A rare case of pediatric intranasal lobular capillary hemangioma - Schild, Sam D.; Irizarry, Rachel; Plum, Ann (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Pediatric nasal cavity vascular tumors express a wide variety of pathologies. Lobular capillary hemangioma (LCH) is an acquired benign vascular growth of skin and mucosa whose etiology remains unknown, though trauma and hormonal influences are implicated. Although well documented in the head and neck literature for children age five or less, it is a rarity within the nasal cavity and has yet to be documented in the mid-septum. We describe a unique case of intranasal LCH and review the current literature. A nine-year-old male presented with one week of profuse intermittent unilateral epistaxis and no history of nasal trauma. Rhinoscopy revealed a pink, pedunculated mass of the right mid-nasal septum at the bony-cartilaginous junction. CT and MRI imaging were consistent with an expansile vascular lesion receiving prominent bilateral sphenopalatine artery supply. Following embolization, en bloc endoscopic surgical excision of the lesion using cold dissection was performed with no bony or cartilaginous involvement noted. The epistaxis resolved following resection. Final histology confirmed the mass as a lobular capillary hemangioma. Paediatric intranasal LCH is a rare entity, yet warrants consideration in our differential diagnosis of pediatric vascular tumors. Our study indicates these lesions can develop in the mid-septum despite the absence of a vascular plexus. Preoperative embolization should be considered for pediatric nasal cavity tumors due to concern for hemorrhage. Endoscopic wide local excision is an appropriate and effective treatment.